2014
DOI: 10.1111/tmi.12406
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in nutritional status of HIV‐exposed children in Rwanda: a longitudinal study

Abstract: Abstractobjective To examine sex differences in nutritional status in relation to feeding practices over time in a cohort of HIV-exposed children participating in a complementary feeding programme in Rwanda.methods We applied a longitudinal design with three measurements 2-3 months apart among infants participating in a complementary feeding programme who were 6-12 months old at baseline. Using early feeding practices and a composite infant and child feeding index (ICFI) as indicators of dietary patterns, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 18 publications
4
24
1
Order By: Relevance
“…It might be due to preferences in feeding practices or other types of exposures [70]. The findings could also be because boys are expected to grow at a slightly more rapid rate compared to girls, and their growth is perhaps more easily affected by nutritional deficiencies or other exposures [71].…”
Section: Discussionmentioning
confidence: 99%
“…It might be due to preferences in feeding practices or other types of exposures [70]. The findings could also be because boys are expected to grow at a slightly more rapid rate compared to girls, and their growth is perhaps more easily affected by nutritional deficiencies or other exposures [71].…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to preferences in feeding practices or other types of exposures (67). It could also be explained by the fact that boys are expected to grow at a slightly more rapid rate compared to girls and their growth is perhaps more easily affected by nutritional deficiencies or other exposures (68).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed that male children are more likely to be stunted than female children (Kandala et al, 2011;Condo et al, 2015;Mukabutera et al, 2016). The odds of stunting increased as the age of children increased.…”
Section: Discussionmentioning
confidence: 94%
“…Previous Rwanda DHS surveys (INSR & Macro, 2006;NISR et al, 2010), showed similar patterns, with a notable difference in the prevalence of stunting among boys and girls: 47.4% boys were stunted compared to 41.4% stunted girls in the RDHS 2010, and in RDHS 2005, 46.3% boys were stunted compared to 44.4% stunted girls. In a study on sex differences in the nutritional status of HIVexposed children in Rwanda, Condo et al (2015) found significant differences in stunting status, with male children being more stunted than their female counterparts. However, in multivariate analysis, the authors did not find a significant difference in feeding practices between males and females children (Condo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation